Supporting vulnerable children in the early years: practical guidance and strategies for working with children at risk - Beckley, Pat (Jessica Kingsley Publishers, 2019)
"Exploring specific experiences, circumstances and events that can put children at risk, this book provides practical guidance for early years practitioners working with vulnerable children. It covers supporting children who are abused and neglected, those with special educational needs, children from ethnic minorities, those with emotional or health difficulties, children affected by poverty and children in care. Each chapter draws on current research and theories to set out clear advice and strategies for supporting the wellbeing and development of vulnerable children, including working in partnership with parents, carers and communities" --